El maestro en formación y la práctica de actividad física: una perspectiva integral (2019)
Of reflection and description, this article aims to give a new meaning the practice of physical education from an inclusive perspective for teacher training; where this is actually participate in physical activities that teach in the classroom, creating   a culture of learning from their own knowledge. Within the theoretical considera- tions, arose the review of different authors related to the topic of work as well as a descriptive methodology - interpretation that allowed the structured analysis of the information collected in the work of field. As important finding, refers to the indispensable need to relate theoretical knowledge concerning physical education with the daily lives of teachers in training for the degree course in basic education (LËB), and the practice of physical activity aiming to create the culture of ethics and professional authority.